The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/s22134849
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Fog–Blockchain Computing for Autonomous-Vehicle-Parking System: A Solution to Reinforce IoT–Cloud Platform for Future Smart Parking

Abstract: With the advent of modern technologies, including the IoT and blockchain, smart-parking (SP) systems are becoming smarter and smarter. Similar to other automated systems, and particularly those that require automation or minimal interaction with humans, the SP system is heuristic in delivering performances, such as throughput in terms of latency, efficiency, privacy, and security, and it is considered a long-term cost-effective solution. This study looks ahead to future trends and developments in SP systems an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…A lightweight, integrated Blockchain and cryptography (LIBC) module at each fog node authorizes and grants AV access in every parking phase to meet privacy and security concerns. A proof-of-concept implementation of the proposed SAVP system showed that its average response time, efficiency, privacy, and security were very good, opening the way for a proven system [136,137]. The authors in [138] proposed a cross-domain solution for the Cognitive Internet of Vehicles to achieve ultra-flow delay and ultra-high dependability in autonomous driving.…”
Section: Cloud Computingmentioning
confidence: 99%
“…A lightweight, integrated Blockchain and cryptography (LIBC) module at each fog node authorizes and grants AV access in every parking phase to meet privacy and security concerns. A proof-of-concept implementation of the proposed SAVP system showed that its average response time, efficiency, privacy, and security were very good, opening the way for a proven system [136,137]. The authors in [138] proposed a cross-domain solution for the Cognitive Internet of Vehicles to achieve ultra-flow delay and ultra-high dependability in autonomous driving.…”
Section: Cloud Computingmentioning
confidence: 99%
“…The study improves the current IoT-cloud platform for AVs utilizing fog-blockchain technologies, putting a special emphasis on QoS, low latency, system efficiency, and security. The deployment of the inclusive, long-term, successful, and high-performing SAVP system makes an SP solution possible [17]. For IoTRec, a system that enables drivers to assess predicted availability of parking spaces and routes.…”
Section: Findings and Analysismentioning
confidence: 99%
“…The detection of data-tampering attack is performed here using data mass and scoring for anomaly detection as a part of intrusion detection. An autonomous vehicle smart-parking system with the fog–blockchain architecture is presented by Shahzad A. et al [ 28 ]. Smart parking helps to recognize the parking location with the help of fog nodes to IoT, the proof-of-concept by lightweight blockchain and a cryptographic module is utilized.…”
Section: Literature Surveymentioning
confidence: 99%